Creating Place out of Space: James Cook's Travel Writing - Klepač, Tihana (Array, 2007)
“ National identity” claims Richard White “ is an invention, ” it is an “ intellectual construct” (Inventing Australia), and Brennan adds that its component elements are race, geography, tradition, history, language, size, and place (“ The National Longing for From” ) ; and place, explains Ashcroft in The Post-Colonial Studies Reader “ in post-colonial societies is a complex interaction of language, history and environment.” It is precisely place that Cook formulates in his journals as he considers the vast, mystical space of the globe, seeing it, as he does all the lands he visited, in terms of Western European rhetoric, thus enabling them to enter history (worlding, Spivak). Therefore, his journals are an important building block in the architecture of both, Australian and North American identity. Namely, before the lands were even settled, Cook’ s writings contributed to the formulation of what it meant to be Australian or North American. This paper is an attempt to analyse Cook’ s discourse in the context of the Western European civilising mission resulting from the Enlightenment, a project which erased earlier knowledges of those lands and overlaid them with those of eighteenth-century Europe.